Assessment of the need of a waiting period after pulmonary vein isolation with the ablation index software. (14th June 2022) - Sousa, Pedro A.; Barra, Sérgio; Adão, Luís; Primo, João; Khoueiry, Ziad; Puga, Luís; Lebreiro, Ana; Fonseca, Paulo; Lagrange, Philippe; Gonçalves, Lino; ,
Abstract: Purpose: Since the widespread availability of contact‐force sensing catheters, the need for a waiting period after pulmonary vein isolation (PVI) has not been reassessed. We aim to evaluate whether a waiting period is still necessary after PVI guided by the ablation Index (AI). Methods: Prospective, multicenter, randomized study of consecutive patients referred for paroxysmal atrial fibrillation (AF) ablation from May 2019 to February 2020. Patients were randomized in a 1:1 ratio to PVI with versus without a waiting period of 20 min. Acute pulmonary vein (PV) reconnection after adenosine challenge was the primary endpoint. A per‐protocol analysis was designed to determine whether a strategy of dismissing the waiting period after PVI was noninferior to waiting for 20 min for identifying acute PV reconnection. PVI was guided by tailored AI values and an interlesion distance ≤6 mm. Results: During the enrollment period, 167 patients (56% males, mean age of 57 ± 14 years) fulfilled the study inclusion criteria – 84 patients (308 PV) in the waiting period group (Group A) and 83 patients (314 PV) in the group without a waiting period (Group B). Acute PV reconnection was identified in 3.8% (95% confidence interval [CI], 1.7%–5.9%) of PVs in the study group B compared to 2.9% (95% CI, 1.0%–4.8%) of PVs in the Group A ( p  = .002 for non‐inferiority). At 1‐year follow‐up, there was no significant difference in arrhythmia recurrence between groups (9.5% in Group A vs. 9.6% in Group B, hazard ratio: 1.03 [95% CI, 0.39–2.73], p  = .98). Conclusion: In paroxysmal AF patients submitted to ablation, a tailored PVI guided by the AI rendered a 20‐min waiting period unnecessary.